2008
DOI: 10.1111/j.1751-1097.2008.00387.x
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the Inactivation by 254 nm Ultraviolet Radiation of Bacteria with Particular Relevance to Biodefense

Abstract: Our goal was to ultimately predict the sensitivity of untested bacteria (including those of biodefense interest) to ultraviolet (UV) radiation. In this study, we present an overview and analysis of the relevant 254 nm data previously reported and available in the literature. The amount of variability in this data prevented us from determining an ''average'' response for any bacterium. Therefore, we developed particular selection criteria to include the data in our analysis and suggested future guidelines for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
134
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 141 publications
(139 citation statements)
references
References 50 publications
4
134
1
Order By: Relevance
“…, reviewed in Table 1 of Coohill and Sagripanti 2008 Peccia et al 2001). This difference in the aerodynamic diameter of vegetative cells could account for different UV sensitivities measured in this and in previous studies.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…, reviewed in Table 1 of Coohill and Sagripanti 2008 Peccia et al 2001). This difference in the aerodynamic diameter of vegetative cells could account for different UV sensitivities measured in this and in previous studies.…”
Section: Discussionmentioning
confidence: 88%
“…Our measurements demonstrated that after 1 min mixing inside the chamber, samples of air at three different locations contained viable bacteria that differed in concentration less than 1.6% between sites. In addition, the curves of semi-logarithmic UV inactivation versus time appearing approximately linear without apparent "toes," (Coohill and Sagripanti 2008) indicate that our samples consisted in relatively homogeneous cell populations. Since the effect of UV intensity on cell inactivation is generally linear through a relatively broad range, cell survival can be extrapolated to other UV dose.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations